2017
DOI: 10.3390/ma10070726
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Fabrication of Highly Porous Titanium Bio-Scaffold with a Load-Bearable Property

Abstract: Porous titanium (P_Ti) is considered as an effective material for bone scaffold to achieve a stiffness reduction. Herein, biomimetic (bio-)scaffolds were made of sintered P_Ti, which used NaCl as the space holder and had it removed via the hydrothermal method. X-ray diffraction results showed that the subsequent sintering temperature of 1000 °C was the optimized temperature for preparing P_Ti. The compressive strength of P_Ti was measured using a compression test, which revealed an excellent load-bearing abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In Figure 6b, we illustrate a practical use of Sr 0.5 -P-Ti_55 in a continuous process for biodiesel conversion and production. With the porosity and considerable mechanical strength of P-Ti_55 and appropriate amount of SrO bonded with Ti-based matrix, an appropriate oil flowing speed penetrating into the porous matrix and reaction with the firmly attached SrO is feasible [13,14]. The Sr 0.5 -P-Ti_55 is thus promising to be employed in a continuous process for biodiesel conversion and production [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 6b, we illustrate a practical use of Sr 0.5 -P-Ti_55 in a continuous process for biodiesel conversion and production. With the porosity and considerable mechanical strength of P-Ti_55 and appropriate amount of SrO bonded with Ti-based matrix, an appropriate oil flowing speed penetrating into the porous matrix and reaction with the firmly attached SrO is feasible [13,14]. The Sr 0.5 -P-Ti_55 is thus promising to be employed in a continuous process for biodiesel conversion and production [12].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, porous Ti with different forms or ratios of porosity has been fabricated using a hydrothermal procedure by the adjustment of NaCl content in Ti powder [13]. Hydrothermal method has been applied for producing a porous Ti-based scaffold at high temperature and high pressure with the inclusion of a removable pore former [13]. Besides, with the increasing demand for complex designs (e.g., a catalytic surface on/in the porous structure/shape), a catalyst coating can be infused [14].…”
Section: Introductionmentioning
confidence: 99%
“…By reducing the strut diameter, a decrease of the homogenised elastic modulus could be obtained [26]. It has been suggested that an implantable and load bearing scaffold should have a compressive strength of higher then 70 Mpa [51]. However, it has been also proclaimed that, human trabecular bone has a modulus ranging from 0.01–2 Gpa [52] and the modulus of a scaffold should be within the range of trabecular bone.…”
Section: Discussionmentioning
confidence: 99%
“…60 There are still many other methods such as Ti-Co and Ti-Mo alloy porous structures through gel-casting by Donghua Yang, 61 as well as porous Ti made by a hydrothermal method. 62 However, here in this review, only those focused on orthopedic application were emphasized. Apart from the suitable biomechanics brought by this kind of method, different densities of the bottom and top parts also offered primary inspiration for functional graded design.…”
Section: Manufacturing Of Tantalum and Porousmentioning
confidence: 99%